TRAINING OF THE UTILIZATION OF OIL PALM MIDRIB AS A CREATIVE BUSINESS TO SUPPORT THE ECONOMY OF THE NAKAU VILLAGE COMMUNITY - Melly Susanti; Ermy Wijaya; Iswidana Utama Putra; Sulisti Afriani; Nopriansah (Kusuma Negara Business School, 2020)
The training was held with the aim of providing direct insight into the community related to the use of oil palm frond waste as a productive product and has a sale value. The training carried out in the village of Nakau, Bengkulu Tengah Regency provided insight into the process and results of the utilization of palm oil waste. This training was given to PKK mothers in the village of Nakau, Bengkulu district, Bengkulu province. The training is carried out by providing a simulation of making products and continuing to design independently. Through this activity the community is expected to be able to utilize the waste and farmers have a solution to the waste of oil palm fronds.